Золотой дождь: [роман] / Виталий Гадиятов - Гадиятов Виталий Галияскарович (Сибирский приключенческий роман, 2018)
Экземпляры: ф.6 (20190722) / Инвентарный номер: 3363zzz / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44